2020
DOI: 10.1111/cas.14514
|View full text |Cite
|
Sign up to set email alerts
|

Expression of classical human leukocyte antigen class I antigens, HLA‐E and HLA‐G, is adversely prognostic in pancreatic cancer patients

Abstract: The expression of classical human leukocyte antigen class I antigens (HLA‐I) on the surfaces of cancer cells allows cytotoxic T cells to recognize and eliminate these cells. Reduction or loss of HLA‐I is a mechanism of escape from antitumor immunity. The present study aimed to investigate the clinicopathological impacts of HLA‐I and non–classical HLA‐I antigens expressed on pancreatic ductal adenocarcinoma (PDAC) cells. We performed immunohistochemistry to detect expression of HLA‐I antigens in PDAC using 243 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 48 publications
1
35
0
1
Order By: Relevance
“…These articles were published between 1998 and 2020, among which 20 were conducted in China, 3 were conducted in Japan, 1 was conducted in Turkey, 2 were conducted in the Netherlands, 2 were conducted in Iran, 1 was conducted in Australia, and 1 was conducted in Italy. Of the 30 articles included in the meta-analysis, there were 12 studies on CRC ( 24 , 30 36 , 38 , 43 , 45 , 46 ), 6 studies on GC ( 25 , 28 , 39 , 41 , 42 , 47 ), 5 studies on ESCC ( 7 , 12 , 48 50 ), 5 studies on HCC ( 26 , 27 , 29 , 37 , 51 ), and 2 studies on PC ( 52 , 53 ). Among them, one study specifically addressed COAD ( 31 ), one study addressed RC ( 30 ), and one addressed both HCC and PAAD ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…These articles were published between 1998 and 2020, among which 20 were conducted in China, 3 were conducted in Japan, 1 was conducted in Turkey, 2 were conducted in the Netherlands, 2 were conducted in Iran, 1 was conducted in Australia, and 1 was conducted in Italy. Of the 30 articles included in the meta-analysis, there were 12 studies on CRC ( 24 , 30 36 , 38 , 43 , 45 , 46 ), 6 studies on GC ( 25 , 28 , 39 , 41 , 42 , 47 ), 5 studies on ESCC ( 7 , 12 , 48 50 ), 5 studies on HCC ( 26 , 27 , 29 , 37 , 51 ), and 2 studies on PC ( 52 , 53 ). Among them, one study specifically addressed COAD ( 31 ), one study addressed RC ( 30 ), and one addressed both HCC and PAAD ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a third explanation, non-classical HLA molecules in EwS could be indicators of inflammatory components of the TME, without making any active contributions to immune inhibition. While a vast number of reports exist that associate either HLA-G or HLA-E with relapse and poor clinical outcome [19,25,[41][42][43][44], evidence for the capacity of these molecules to suppress antitumor responses by CD8+ T cells remains limited. To our knowledge, this is the first report addressing the potency of either HLA-G or HLA-E to impair CART-mediated antitumor responses.…”
Section: Discussionmentioning
confidence: 99%
“…Ever increasing studies on HLA-G expression by solid tumor lesions have revealed that high levels of HLA-G expression was associated with advanced disease stage, tumor metastasis, poor prognosis, or shorter disease-free survival. However, either among patients with different types of cancers, or among patients with the same type of cancer, intertumor and intratumor heterogeneity of HLA-G expression is evident, such as among patients with breast cancer ( 6 15 ), colorectal cancer ( 16 24 ), cervical cancer ( 25 27 ), endometrial cancer ( 28 31 ), esophageal squamous cell carcinoma ( 32 34 ), Ewing sarcoma ( 35 ), gastric cancer ( 36 38 ), glioblastoma ( 39 ), hepatocellular carcinoma ( 40 42 ), lung cancer ( 43 45 ), classical Hodgkin lymphoma ( 46 , 47 ), diffuse large B-cell lymphoma ( 48 ), cutaneous T- and B-cell lymphoma ( 49 ), nasopharyngeal carcinoma ( 50 ), oral squamous cell carcinoma ( 51 ), ovarian cancer ( 52 – 55 ), pancreatic adenocarcinoma ( 56 59 ), and thyroid cancer ( 60 , 61 ) ( Table 1 ). HLA-G expression in solid cancers is now well acknowledged in promoting cancer cell immune escaping and tumor development, and associated with disease progression and poor survival either among cancer patients or pre-clinical murine models ( 62 ).…”
Section: Introductionmentioning
confidence: 99%